The Effectiveness Using The Indonesian Warship Parchim Class in order to Support the Maritime Security Operations at Natuna Sea - Rudi Iskandar (PUSJIANMAR SESKOAL, 2020)
In order to support the successful implementation of the Indonesian Navy's main tasks, the readiness of the Indonesia warships (KRI), which includes preparedness in the Platform, Sewaco and the capabilities of its personnel, are expected to have high combat readiness. The purpose of this study is to analyze the effectiveness of the use of KRI Parchim class in supporting the Maritime Security operations and develop concepts to increase the KRI readiness of Parchim class. The study was conducted using qualitative methods of data collection techniques through direct interviews with the relevant informants, documentation as supporting data collected as a reinforcement of observation and interview data, data reduction to select and sort basic data in accordance with the research, data verification that has been collected and verified for its correctness. The results of the analysis using the SWOT method with internal and external factors obtained from the interviews, it can be concluded that the KRI Parchim class still needs to be maintained to carry out sea security patrols as seen from the ability of the platform. However, Sewaco is still considered capable and feasible to cover Indonesian waters.Keywords: effectiveness, readiness, Indonesian Navy, operations, marine security